1989
DOI: 10.1002/path.1711580110
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature and conventional scanning electron microscopy of human urothelial neoplasms

Abstract: The appearance of neoplastic human urothelium viewed by low-temperature scanning electron microscopy (LTSEM) and conventional scanning electron microscopy (CSEM) was compared. Fixed, dehydrated neoplastic cells viewed by CSEM had well-defined, often raised cell junctions; no intercellular gaps; and varying degrees of pleomorphic surface microvilli. The frozen hydrated material viewed by LTSEM, however, was quite different. The cells had a flat or dimpled surface, but no microvilli. There were labyrinthine late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…There is potential for the application of LTSEM and XRMA in the determination of electrolyte changes associated with disease processes. Despite numer-ous technical difficulties associated with the technique [l-31, studies of electrolyte levels in neoplastic and nonneoplastic human urothelium have been carried out successfully [3,7,121. From these studies, it has been found that the electrolyte ratios Kf/P, K+/Na+, and Kf/CIin neoplastic cells are significantly higher than in nonneoplastic cells.…”
mentioning
confidence: 99%
“…There is potential for the application of LTSEM and XRMA in the determination of electrolyte changes associated with disease processes. Despite numer-ous technical difficulties associated with the technique [l-31, studies of electrolyte levels in neoplastic and nonneoplastic human urothelium have been carried out successfully [3,7,121. From these studies, it has been found that the electrolyte ratios Kf/P, K+/Na+, and Kf/CIin neoplastic cells are significantly higher than in nonneoplastic cells.…”
mentioning
confidence: 99%